Perioperative Infection Transmission: the Role of the Anesthesia Provider in Infection Control and Healthcare-Associated Infections - Sharma, Archit (Curr Anesthesiol Rep, 2020)
PURPOSE OF REVIEW: This review aims to highlight key factors in the perioperative environment that contribute to transmission of infectious pathogens, leading to healthcare-associated infection. This knowledge will provide anesthesia providers the tools to optimize preventive measures, with the goal of improved patient and provider safety. RECENT FINDINGS: Over the past decade, much has been learned about the epidemiology of perioperative pathogen transmission. Patients, providers, and the environment serve as reservoirs of origin that contribute to infection development. Ongoing surveillance of pathogen transmission among these reservoirs is essential to ensure effective perioperative infection prevention. SUMMARY: Recent work has proven the efficacy of a strategic approach for perioperative optimization of hand hygiene, environmental cleaning, patient decolonization, and intravascular catheter design and handling improvement protocols. This work, proven to generate substantial reductions in surgical site infections, can also be applied to aide prevention of SARS-CoV-2 spread in the COVID-19 era.